New records of grison (Galictis vittata) in Campeche, México - Contreras-Moreno, Fernando M.; Jesús-Espinosa, Daniel; Cruz-Romo, Lizardo; Méndez-Saint Martin, Gabriela; Tamay Yah, Luis A.; Sánchez-Pinzón, Khiavett G.; Delgado-Martínez, Carlos M.; Mendoza, Eduardo; Dræby, Klaus; Uc-Monrrero, Evelio (Therya Notes, 2023)
The grison is a carnivorous mammal of the family Mustelidae listed as threatened in Mexico. There are few records and information on different aspects of its ecology. The objective of this note was to report new records of grison in Campeche. From January 2017 to June 2022, 30 camera-trap stations were installed in natural and artificial water bodies within the Calakmul Biosphere Reserve to capture and identify wildlife. Additionally, roadkilled individuals were recorded by vehicle tours along the Campeche roads. Records were also searched in international databases, books, and published articles. With a sampling effort of 15,000 camera trap nights, we captured 2 separate grison photographs in the Calakmul Biosphere Reserve and 6 records of roadkilled animals in Campeche. This note documents the presence of grison in several habitats of Campeche. The lack of information on the species might be due to multiple reasons. The sampling methods target large animals and the greatest sampling efforts are performed in protected natural areas with a high conservation level. We found that most records correspond to disturbed sites with secondary vegetation. The fact that many records were of roadkilled animals suggests that this species is susceptible to the impact of roads in Campeche.